CHANGES IN SOIL CHEMICAL PROPERTIES AND TOMATO CROPS YIELD GIVEN MARKET WASTE COMPOST LEASE - Suleman, Darwis; Alam, Syamsu; Rustam, La Ode; Setiawan, Agus (Universitas Veteran Bangun Nusantara, 2025)
Long-term use of chemical fertilizers could accelerate the decline in soil quality, while organic waste from fruit markets in Kendari City increases every year in line with the increase of population. In this regard, the goal of this study was to evaluate the effect of leachate from fruit market waste compost on several soil chemical properties and tomato yield on Ultisol. The study was carried out on experimental farm at the Faculty of Agriculture, Halu Oleo University from December 2021 to February 2022. This study used a randomized block design consisted of 4 treatments, namely: No leachate (P0), 200 ml polybag-1 (P1), 400 ml polybag-1 (P2), 600 ml polybag-1 (P3). The results highlighted that the application of leachate from fruit market waste increased organic C, total N, available P and total K in the soil linearly. The highest increase was achieved when applying 600 ml per polybag-1 (P3) of leachate by 49.83%, 42.85%, 71.68% and 72.82% over the control (P0). Application of leachate improved the plant height, number of branches, number of fruit and fruit weight compared to other treatments. The highest number of fruit and the heaviest fruit weight were recorded when supplementing 600 ml of polybag-1 leachate by 6.33 pieces and 85.60 g. Keywords: Leachate, organic C, tomato, ultisol